2019
DOI: 10.3390/ma12071147
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Aggregate-Paste Interface by the Hydration of Steelmaking Waste in Concretes and Mortars

Abstract: The objective of the experimental work is to study the mechanical properties in self-compacting concretes (SCC) in which part of the limestone aggregate has been replaced by granulated blast furnace slag (GBFS) in different percentages ranging from 0% to 60%. The results show that at early ages the SCC with the largest content in slag tend to have lower compressive strengths due to the poor compacting of the aggregates, although in the long-term their strength increases due to the reactivity of the slag. In fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In addition, although ultrafine GGBS can improve strength and durability, the addition of new materials to GGBS can increase these properties [55]. Furthermore, the mechanical properties in Self-Compacting Concretes (SCC), replaced by Granulated Blast Furnace Slag (GBFS) in the limestone aggregate from 0% to 60%, have been analysed [56]. Going into detail, it was found that the replacement in mortar the 50% of cement with ground GBFS produced a compressive strength similar to the reference mortar, containing 100% of cement.…”
Section: By-products Reuse In Cement Productionmentioning
confidence: 99%
“…In addition, although ultrafine GGBS can improve strength and durability, the addition of new materials to GGBS can increase these properties [55]. Furthermore, the mechanical properties in Self-Compacting Concretes (SCC), replaced by Granulated Blast Furnace Slag (GBFS) in the limestone aggregate from 0% to 60%, have been analysed [56]. Going into detail, it was found that the replacement in mortar the 50% of cement with ground GBFS produced a compressive strength similar to the reference mortar, containing 100% of cement.…”
Section: By-products Reuse In Cement Productionmentioning
confidence: 99%
“…An area with a higher concentration of Ca, Si and Na atoms can be observed. The presence of Na in the cement zone is very significant, since this element is practically absent in the chemical composition of cement [18], as we have seen in Section 2.1. From the EDS analysis, the main chemical elements of the healing products are Si, O, Ca and Na.…”
Section: Morphology and Microstructurementioning
confidence: 62%
“…It is observed that there is no Ca in the original healing agent "sodium silicate", but there is a transfer of this compound to the cracked area. Since soluble silicates react almost instantaneously with multivalent metal cations to form the corresponding insoluble metal silicate [18], the chemical element Ca in healing products reveals that calcium cations from the cementing matrixes with the sodium silicate solution, and thus, CSH is formed in the cracks. However, there are not enough calcium cations to replace all of the sodium cations in solution.…”
Section: Morphology and Microstructurementioning
confidence: 99%